Psychosocial adversity and allostatic load burden in midlife and older ages. - Mc Crory, Cathal; Kenny, Rose (My University, 2021)
Objective: To investigate the individual and cumulative impact of childhood and adulthood adversity on allostatic load (AL) burden. Method: Retrospective cross-sectional study design involving 4,165 participants from the first wave of The Irish Longitudinal study on Ageing (TILDA). AL was operationalized using 12 biomarkers across four physiological systems (cardiovascular, metabolic, renal, and immune). Measures of psychosocial adversity included poverty, abuse, loss, and illness. Negative binomial regression models estimated the relationship of individual adversities and a cumulative count of adversities with AL burden, controlling for age and sex. Multivariable models adjusted additionally for a range of other sociodemographic and lifestyle factors. Results: Childhood poverty, childhood physical abuse, and having a spouse/partner/child experience a life-threatening illness/accident were associated with 10% (95% CI [1.04, 1,16]), 10% (95% CI [1.01, 1.18]), and 6% (95% CI [1.01, 1.11]) greater AL burden, respectively. Cumulative adversity was associated with 3% (95% CI [1.01, 1.04]) higher AL burden. Adjusting for sociodemographic and lifestyle covariates rendered the association of childhood poverty (IRR= 1.04, 95% CI [.98, 1.09]; p = .190) and childhood physical abuse (IRR= 1.07, 95% CI [.99, 1.15]; p = .081) with AL burden nonsignificant, while the association of having an ill spouse/partner/child on AL persisted (IRR= 1.06, 95% CI [1.01, 1.11]; p = .021). Conclusions: This study provided limited support for the idea that psychosocial stress leads to higher AL, with just three out of 11 adversities associated with AL.
PUBLISHED
Keywords: adversity, allostatic load, stress, physiological dysregulation, life course; Ageing